Learning and Satisfaction in Webinar, Online, and Face-to-Face Instruction: A Meta-Analysis - Ebner, Christian; Gegenfurtner, Andreas (Frontiers in Education, 2019)
Kirkpatrick’s four-level training evaluation model assumes that a positive correlation exists between satisfaction and learning. Several studies have investigated levels of satisfaction and learning in synchronous online courses, asynchronous online learning management systems, and synchronous face-to-face classroom instruction. The goal of the present meta-analysis was to cumulate these effect sizes and test the predictive validity of Kirkpatrick’s assumption. In this connection, particular attention was given to a prototypical form of synchronous online courses – so called “webinars”. The following two research questions were addressed: (a) Compared to asynchronous online and face-to-face instruction, how effective are webinars in promoting student learning and satisfaction? (b) What is the association between satisfaction and learning in webinar, asynchronous online and face-to-face instruction? The results showed that webinars were descriptively more effective in promoting student knowledge than asynchronous online (Hedges’ g = 0.29) and face-to-face instruction (g = 0.06). Satisfaction was negligibly higher in webinars compared to asynchronous online instruction (g = 0.12) but was lower in webinars to face-to-face instruction (g = -0.33). Learning and satisfaction were negatively associated in all three conditions, indicating no empirical support for Kirkpatrick’s assumption in the context of webinar, asynchronous online and face-to-face instruction.